Forceful Federalism against American Racial Inequality - King, D (Cambridge University Press, 2017)
Why, many Americans rightly ask, can material racial inequality and widespread segregation still persist fifty years after the enactment of key civil rights legislation and eight years after the election of an African American to the nation’s highest office? Many from outside the United States pose similar questions about modern America. The explanation, I argue lies with inconsistent and fluctuating levels of federal engagement to building material racial equality. National engagement fluctuates because it is energetically resisted and challenged, by opponents of racial progress. This vulnerability to disruption is exposed by varying strategies of resistance, some fiscal, some violent, some judicial, some desultory and some combining violent protest against change with local electoral triumphs for anti-reformers. Public resistance to employing national resources to reduce inequality encouraged a de-racialization strategy amongst many African American candidates for elected office who opt to de-emphasise issues of racial inequality in campaigns and in office. Whatever the means, the effect is uniform: the slowing down or outright death of federal civil rights activism.